Attenuation of myocardial fibrosis with curcumin is mediated by modulating expression of angiotensin II AT1/AT2 receptors and ACE2 in rats - Pang XF; Zhang LH; Bai F; Wang NP; Garner RE; McKallip RJ; Zhao ZQ (Dove Medical Press, 2015)
Xue-Fen Pang,1 Li-Hui Zhang,2 Feng Bai,1 Ning-Ping Wang,3 Ron E Garner,3 Robert J McKallip,4 Zhi-Qing Zhao1,3 1Department of Physiology, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2Department of Cardiology, Shanxi Academy of Medical Sciences and Shanxi Dayi Hospital, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 3Department of Basic Biomedical Sciences, Mercer University School of Medicine, Savannah, GA, USA; 4Division of Basic Biomedical Sciences, Mercer University School of Medicine, Macon, GA, USA Abstract: Curcumin is known to improve cardiac function by balancing degradation and synthesis of collagens after myocardial infarction. This study tested the hypothesis that inhibition of myocardial fibrosis by curcumin is associated with modulating expression of angiotensin II (Ang II) receptors and angiotensin-converting enzyme 2 (ACE2). Male Sprague Dawley rats were subjected to Ang II infusion (500 ng/kg/min) using osmotic minipumps for 2 and 4 weeks, respectively, and curcumin (150 mg/kg/day) was fed by gastric gavage during Ang II infusion. Compared to the animals with Ang II infusion, curcumin significantly decreased the mean arterial blood pressure during the course of the observation. The protein level of the Ang II type 1 (AT1) receptor was reduced, and the Ang II type 2 (AT2) receptor was up-regulated, evidenced by an increased ratio of the AT2 receptor over the AT1 receptor in the curcumin group (1.2±0.02%) vs in the Ang II group (0.7±0.03%, P<0.05). These changes were coincident with less locally expressed AT1 receptor and enhanced AT2 receptor in the intracardiac vessels and intermyocardium. Along with these modulations, curcumin significantly decreased the populations of macrophages and alpha smooth muscle actin-expressing myofibroblasts, which were accompanied by reduced expression of transforming growth factor beta 1 and phosphorylated-Smad2/3. Collagen I synthesis was inhibited, and tissue fibrosis was attenuated, as demonstrated by less extensive collagen-rich fibrosis. Furthermore, curcumin increased protein level of ACE2 and enhanced its expression in the intermyocardium relative to the Ang II group. These results suggest that curcumin could be considered as an add-on therapeutic agent in the treatment of fibrosis-derived heart failure patient who is intolerant of ACE inhibitor therapy. Keywords: angiotensin II receptors, angiotensin-converting enzyme 2, curcumin, collagen, myocardial fibrosis